Calibration strategy of diesel-fuel spray atomization models using a design of experiment method. (September 2016) - Brulatout, Jonathan; Garnier, François; Mounaïm-Rousselle, Christine; Seers, Patrice
The Reitz and Diwakar and the KHRT atomization models are widely used for high-pressure diesel-fuel spray. The constants in both models must be calibrated to correctly predict the injection process based on the nozzle geometry, injection conditions, and fuel. Calibration can be significantly time-consuming given the four constants in both models. This paper suggests a strategy to assess the impact of models' constants on spray tip penetration and mean droplet-diameter predictions on a reference case, with an injection pressure of 700 bar, to characterize the influence of the atomization model's calibration. The assessment used a design of experiment method (DOE), which demonstrated the important interaction between constants on the results. Obtained calibrations were used for comparing the models' performances qualitatively and quantitatively by accounting for spray and air-entrainment characteristics. Both models gave similar results, but the KHRT model yielded a better spray shape. Finally, based on DOE results, a method is proposed to modify the model's constants for higher pressures (900 and 1300 bar).